1995
DOI: 10.2214/ajr.164.6.7754890
|View full text |Cite
|
Sign up to set email alerts
|

Risk of vertebral fractures in men: relationship to mineral density of the vertebral body.

Abstract: OBJECTIVE.Vertebral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 17 publications
0
12
0
3
Order By: Relevance
“…Decreased bone mineral density because osteoporosis disrupts the bone microarchitecture and alters the contents of noncollagenous proteins in the bone matrix. 15,16 This structural deterioration of the tissue leads to fragile bones that are prone to fractures. It is estimated that approximately 44 million Americans have osteoporosis and that an additional 34 million Americans have low bone mass.…”
Section: Etiology Of Vertebral Compression Fractures Of the Spinementioning
confidence: 99%
See 1 more Smart Citation
“…Decreased bone mineral density because osteoporosis disrupts the bone microarchitecture and alters the contents of noncollagenous proteins in the bone matrix. 15,16 This structural deterioration of the tissue leads to fragile bones that are prone to fractures. It is estimated that approximately 44 million Americans have osteoporosis and that an additional 34 million Americans have low bone mass.…”
Section: Etiology Of Vertebral Compression Fractures Of the Spinementioning
confidence: 99%
“…16 Newer treatment options like bisphonates have been shown to reduce the risk of fractures. 15,21 In randomized clinical trials, alendronate has been found to reduce the risk of vertebral fractures by 50% in postmenopausal women. 3 Other agents with clinical evidence of efficacy include raloxifene, parathormone, and calcitonin.…”
Section: Treatment Of Osteoporosismentioning
confidence: 99%
“…These were taken into account and observed during the tests. Before we conducted the tests, the BMD values of all specimens were determined by DE-QCT, currently considered to be the method of choice [12,15,17,19,26,31,32,33]. However, since the results of series investigations into BMD have shown considerable dispersion, only a range of physiological reference values exist.…”
Section: Discussionmentioning
confidence: 99%
“…After removal, the vertebral bodies were freed of adjoining tissue, sealed in plastic bags and frozen to -18°C. The cortical and cancellous bone mineral densities (BMD cort and BMD canc ) of the specimens were determined in a water-bath by dual-energy quantitative computed tomography (DE-QCT; Somatom plus S, Siemens, Munich-Erlangen, Germany), using OsteoCT software and a reference phantom [12,15,17,19,26,31,32,33]. The end-plates of the individual vertebral bodies were embedded in hard plaster for the trials, and the vertebral body endplates were aligned as horizontally as possible (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Osteoporosis was measured by DEXA scan by using T-scores. The WHO uses T-scores 18 to define normal bone mass, low bone mass (or osteopenia), and osteoporosis. T-score compares bone density to the average bone density of young healthy adults of same gender.…”
mentioning
confidence: 99%